P146Cardioprotection by consecutive isoproterenol/adenosine treatment at clinically relevant concentrations in aged and in failing heart. (15th July 2014) - Khaliulin, I; Halestrap, AP; James, AF; Bryant, SM; Suleiman, MS
Abstract: Purpose: We have recently discovered that consecutive treatment of heart with isoproterenol and adenosine (Iso/Ade treatment), with a high dose of Iso (200 nM), confers strong protection against ischemia and reperfusion injury. Here we investigate whether this effect can be achieved at clinically relevant dose of Iso and identify the mechanism responsible of this intervention.  This intervention has further been investigated using aged hearts and hearts with surgically-induced heart failure.  Methods: Isolated rat hearts were perfused sequentially with 5 nM Iso and 30 μM Ade followed by 0, 5, or 10 min washout prior to 30 min ischemia and 2 hrs reperfusion. Ischaemia/reperfusion injury was assessed by measuring haemodynamic function, lactate dehydrogenase (LDH) release and infarct size. Protein kinase C (PKC) and glycogen content were also measured in these hearts. Additional experiments were carried out in the presence or absence of Cyclosporine A (CsA), a mitochondria permeability transition pore (MPTP) inhibitor. Heart failure was induced by ligation of the left descending anterior coronary artery in 2 months old rats. Heart failure was developed after 16 weeks post-surgery. Sham operated rats served as control. These hearts were subjected to Iso/Ade treatment at clinically relevant concentrations of the drugs followed by ischaemia and reperfusion. The efficacy of this intervention was also tested in 16 months old rats.  Results: Iso/Ade treatment with 5 nM Iso effectively improved hemodynamic function recovery, considerably reduced LDH release, reduced infarct size, increased PKC activity and reduced glycogen content. CsA protected hearts but had no additive effect to the Iso/Ade treatment. Both failing and aged hearts were effectively protected by the Iso/Ade treatment. Conclusions: Consecutive Iso/Ade treatment can be effective at clinically relevant doses of the drugs and the cardioprotective effect of this treatment is not suppressed by age or heart failure and appears to be mediated by the inhibition of MPTP and glycogen depletion in myocardium.